Interpolation Bezier curve modeling of crisp Z-number data - Rozaimi Zakaria (Faculty of Science & Natural Resources, UMS, 2022)
In visualizing data for further research, one of the methods is to model the data set through curves and surfaces. But the problem arises when the data set has an uncertain issue. The issue can be the reliability of the data set. Therefore, in this paper, the defining process of defining and modeling the uncertain data against the reliability of the data will be proposed. The proposed method for defining such a data set is by using the concept of Z-number. For crisp Z-number, the data have the uncertain issue on the reliability whereas the data set is crisp. A numerical example will be given and then modeled through the curve by using the interpolation Bezier curve for more comprehension.